Synthesis and characterization of chiral 6-azaspiro[2.5]octanes as potent and selective antagonists of the M4 muscarinic acetylcholine receptor. (15th January 2022) - Bender, Aaron M.; Carter, Trever R.; Spock, Matthew; Rodriguez, Alice L.; Dickerson, Jonathan W.; Rook, Jerri M.; Chang, Sichen; Qi, Aidong; Presley, Christopher C.; Engers, Darren W.; Harp, Joel M.; Bridges, Thomas M.; et al.
Graphical abstract: Abstract: In this manuscript, we report a series of chiral 6-azaspiro[2.5]octanes and related spirocycles as highly potent and selective antagonists of the muscarinic acetylcholine receptor subtype 4 (mAChR4 ). Chiral separation and subsequent X-ray crystallographic analysis of early generation analogs revealed the R enantiomer to possess excellent human and rat M4 potency, and further structure–activity relationship (SAR) studies on this chiral scaffold led to the discovery of VU6015241 (compound 19 ). Compound 19 is characterized by high M4 potency and selectivity across multiple species, excellent aqueous solubility, and moderate brain exposure in rodents after intraperitoneal administration.